Review of Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition, by M.L. Paine - Baughman, Timothy H (Polar Research, 2008)
If the reader is looking for another rehashing of one of the adventures of the “Heroic Era” of Antarctic exploration, or another reshaping of the same old material about the three or four explorers from that period who get all the attention, M.L. Paine’s Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition is not the book for you. But if you are a serious Antarctic buff who wants to learn something new, and really get inside one of the early expeditions of the 20th century, Paine’s volume will be a compelling read.
Keywords: Antarktis; Richard Evelyn Byrd; Sydpolflyvningen; bokanmeldelser; dagbøker; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving; turisme

Polaroppdraget - Paulsen, Øystein S (Forsvarets forum, 2007)
Keywords: Dronning Maud Land; ekspedisjoner; fly; logistikk

Otter'n, sprækeste fly i verden: skjeggete Antarktis-flygere hjemme igjen etter vellykket kartlegging av norske ismasser - Heyerdahl, Johan Fredrik (Mannskapsavisa, 1959)
Keywords: Dronning Maud Land; ekspedisjoner; fly; kartlegging; logistikk

Norsk-britisk-svensk vitenskapelig ekspedisjon til Antarktis 1949/52. 4 = Norwegian-British-Swedish scientific expedition to the Antarctic 1949/52. 4 - Sverdrup, Harald Ulrik (Norsk hvalfangst-tidende, 1951)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; fly; kartlegging